2014
DOI: 10.4314/njp.v42i1.9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of alcohol consumption among secondary school students in Port Harcourt, Southern Nigeria

Abstract: Background: Consumption of alcohol by secondary school students is a major public health concern globally, but its prevalence is not known in secondary schools in Port Harcourt. Objective: To determine the prevalence and factors associated with alcohol use among secondary school students in Port Harcourt. Methods: This was a cross sectional school based study conducted in Port Harcourt in March 2014. A 20 itemed structured, self-administered questionnaire was distributed to 1080 senior secondary 1 to 3 student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 8 publications
4
23
2
Order By: Relevance
“…Finally, our findings also showed that male and female students had similar levels of awareness of the following effects of alcohol on human health, as no significant differences were found: excessive alcohol intake can affect coordination, interfering with balance and the ability to walk; heavy alcohol use can result in alcohol dependence; alcohol use can make people with depression feel worse; and erectile dysfunction is a side effect of alcohol abuse in men. These outcomes support previous studies, [ 1 , 9 ] which show that alcohol increases the risk of numerous diseases and all injury outcomes. According to the WHO, [ 2 ] alcohol consumption is now the world's third largest risk factor for disease and disability, with almost 4% of all global deaths attributed to alcohol.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Finally, our findings also showed that male and female students had similar levels of awareness of the following effects of alcohol on human health, as no significant differences were found: excessive alcohol intake can affect coordination, interfering with balance and the ability to walk; heavy alcohol use can result in alcohol dependence; alcohol use can make people with depression feel worse; and erectile dysfunction is a side effect of alcohol abuse in men. These outcomes support previous studies, [ 1 , 9 ] which show that alcohol increases the risk of numerous diseases and all injury outcomes. According to the WHO, [ 2 ] alcohol consumption is now the world's third largest risk factor for disease and disability, with almost 4% of all global deaths attributed to alcohol.…”
Section: Discussionsupporting
confidence: 91%
“…Through in-person interviews with Nigerian adults, previous research by Gureje et al [ 3 ] revealed that the lifetime prevalence of alcohol consumption was 56%. A recent study by Alex-Hart et al [ 9 ] showed that the prevalence of current alcohol consumption among a sample of Nigerian secondary school students was 30.6% and that 38.1% of current drinkers had also been drunk in the past 30 days, with 17.2% being drunk very frequently.…”
Section: Introductionmentioning
confidence: 99%
“…While 46.2% of undergraduate students of Adekunle Ajasin University, Akungba-Akoko, Ondo state, Nigeria still drink alcoholic beverages, although the level and rate of consumption differs. This result disagrees with [10], whose study revealed that the predominance of current alcohol use among a sample of Nigerian optional school students was 30.6%, and that 38.1% of current consumers had likewise been drunk in the previous 30 days, with 17.2% being drunk most of the time. Although, this study agrees with [7], who's investigation among 292 out-of-school male youths in an urban territory of Central Nigeria (aged 11 to 20 years) found that in excess of 33% (38.7%) of the sample had taken alcohol at any rate once in their lives.…”
Section: Discussion Of Findingscontrasting
confidence: 87%
“…Furthermore, through a face-to-face interviews with some Nigerian adolescents, past research by [9] uncovered that the lifetime pervasiveness of alcohol use was 56%. In addition, a report by [10] demonstrated that the predominance of current alcohol use among a sample of Nigerian optional school students was 30.6% and that 38.1% of current consumers had likewise been drunk in the previous 30 days, with 17.2% being drunk most of the time. Despite the major health problem that arises from drinking of excessive alcohol; for example, cancer [11], pancreatitis, liver cirrhosis, tuberculosis, pneumonia, diabetes mellitus, malignancies, mental horribleness, and injury [12], students still indulges in the drinking of alcohol.…”
Section: Introductionmentioning
confidence: 99%
“…However, using the anonymous self-report, confidentiality guaranteed (Althubaiti, 2016) and large sample size as validated instrument for assessment as well as informing participants about the objective and giving them much time before answering (Eman, 2005) the questionnaire can minimize this possibility. Previous studies have shown that the prevalence of alcohol consumption was higher among boy than girls (Alex-Hart, Opara, & Okagua, 2015;Assanangkornchai et al, 2010;Chaveepojnkamjorn, 2012;MacArthur et al, 2012;Pengpid & Peltzer, 2012;Phuphaibul, Nuntawan, & Loveland-Chery, 2011;Pichainarong & Chaveepojnkamjorn, 2010;Sam-angsri et al, 2010;Simoes, Batista-Foguet, Matos, & Calmeiro, 2008). In this research study, conversely, girl participants were more likely to engage in alcohol use than boys.…”
Section: Discussionmentioning
confidence: 42%